Impaired adult olfactory bulb neurogenesis in the R6/2 mouse model of Huntington's disease - Winner, Beate; Kohl, Zacharias; Regensburger, Martin; Kandasamy, Mahesh; Winkler, Jürgen; et al. (BMC Neuroscience, 2010)
Background: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder linked to expanded CAG-triplet nucleotide repeats within the huntingtin gene. Intracellular huntingtin aggregates are present in neurons of distinct brain areas, among them regions of adult neurogenesis including the hippocampus and the subventricular zone/olfactory bulb system. Previously, reduced hippocampal neurogenesis has been detected in transgenic rodent models of HD. Therefore, we hypothesized that mutant huntingtin also affects newly generated neurons derived from the subventricular zone of adult R6/2 HD mice.Results: We observed a redirection of immature neuroblasts towards the striatum, however failed to detect new mature neurons. We further analyzed adult neurogenesis in the granular cell layer and the glomerular layer of the olfactory bulb, the physiological target region of subventricular zone-derived neuroblasts. Using bromodeoxyuridine to label proliferating cells, we observed in both neurogenic regions of the olfactory bulb a reduction in newly generated neurons.Conclusion: These findings suggest that the striatal environment, severely affected in R6/2 mice, is capable of attracting neuroblasts, however this region fails to provide sufficient signals for neuronal maturation. Moreover, in transgenic R6/2 animals, the hostile huntingtin-associated microenvironment in the olfactory bulb interferes with the survival and integration of new mature neurons. Taken together, endogenous cell repair strategies in HD may require additional factors for the differentiation and survival of newly generated neurons both in neurogenic and non-neurogenic regions.